Bed erosion below overflowing weir with an apron - Fang, Siqin. (2011)
The project is conducted to investigate the scouring phenomenon at the downstream of an overflowing weir with and without an apron. Apart from studying the changes in the general bed scour profile, the equilibrium scour condition is the key focus. This is achieved by reviewing the concepts that were critical to the study. Following which, the study was completed by conducting 28 experiments on a 8.0m long by 0.3m wide by 0.6m deep flume where the scour profiles were being periodically recorded during the experiment. Nevertheless, the experiments were conducted by focusing on the effect of varying flowrate, water depth differences and apron length; other parameters were left constant. The results show that the formation of scour hole is dependent on the three mentioned parameters whereas the increase in flowrate, increase in water depth differences and decrease in apron length will all lead to an increase in the scour depth. Empirical correlations were established to predict the equilibrium scour time, equilibrium maximum scour depth and scour-time development with flowrate and water depth differences. The accuracy of the prediction is as high as 80% of the actual depth which is deemed to be within the satisfaction limit. It was found that the apron must have a minimum length so that the plunging nappe will not strike the erodible bed. In addition, the scour depth can be reduced by almost 80% when the apron length to water depth above the weir crest ratio approaches a certain magnitude.